A study of the responses of women in Laoag during the Japanese occupation, 1942-1945 - Almazan, Menard S. (1997)
Being an undertaking in local history, this study focuses on the conditions and responses of women in Laoag during the Japanese occupation, 1942-1945. For this study the historical methodology used key informant interviews in gathering data. The analysis was based on the framework on resistance and responses. The study concluded that women in Laoag were active participants during the Second World War -- Author's abstract.
Thesis (Bachelor of Arts in Social Sciences) -- University of the Philippines Baguio, 1997.
Includes bibliographical references.
Keywords: Women guerrillas -- Philippines -- Laoag; Laoag -- History -- Japanese occupation -- 1942-1945.